Unveiling the metal-insulator transition at YTiO3/LaTiO3 interfaces grown by the soft chemical method - Tolentino Cabral, Ana Cristina; Tafur Tanta, Urbano Miguel; Simões, Alexandre Zirpoli [UNESP]; Bastos, Wagner; Moreno, Henrique [UNESP]; Ramirez, Miguel Angel [UNESP]; Ponce, Miguel Adolfo; Moura, Francisco (Elsevier, 2023)
In the last couple of years, perovskites and transition metal oxides have demonstrated high potential for energy storage/processing applications. Oxide interfaces with piezoelectric, magnetic and metal-insulator transition based on YTiO3/LaTiO3 heterostructured films were investigated in this work. The Mott insulator, YTiO3, was deposited onto a Mott insulator, LaTiO3, via polymeric precursor method. Spin coating was performed to obtain a YTiO3/LaTiO3 heterostructed thin films deposited onto Pt/TiO2/SiO2/Si substrates. Structure, morphology, and electrical properties of the films were assessed. The YTiO3/LaTiO3 heterostructures exhibit ferromagnetic and piezoelectric behavior (d33máx≈8.11 p.m./V), which may be attributed to smaller grain (average grain size≈20.00 nm) and, thus, a higher grain boundary density, and stress in the film plane due to the different properties of the interface. The dielectric permittivity and dielectric loss at 1 KHz were found to be 70 and 0.41, respectively. I–V measurements on different electrode areas confirmed a metal-to-insulator transition, indicating a potential aplication in correlated electron random access memory (CeRAM).
Keywords: Magnetic properties; Metal-insulator transition; Perovskite; Piezoelectric properties; Polymeric precursor method